The Guidelines of Area Arrangement within the Early Childhood Classroom Supporting Child-Centered Learning - Chaiyarak, Vitsanee; Phanthong, Wilaiwan (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2021)
This research aimed to study the factors affecting area arrangement and the guidelines of area arrangement within the early childhood classroom supporting child-centered learning. There were three schools under the Office of the Basic Education Commission, Nakhon Ratchasima Province, involved in this study, i.e. Ban Krathum Rai School, Ban Nong Doen School and Ban Nong Takhlong School. Research tools include questionnaires, evaluation, observation and interview form. Statistical analysis were means ( ), standard deviations (S.D.) and percentage. The research found that 1) Factors affecting area arrangement within the early childhood classroom consisted of movement and rhythm activities, experience enhancing activities, creative arts activities, free activities or play corners and educational game activities. The space in the classroom was divided into four parts. The first part was provided for the teachers while the second part was for students’ personal storage. The third part was the area for play corner activities. The fourth part was the space at the center of the room as the area for learning, sleeping, eating, movement and rhythm activities. The furniture in the classroom should be lightweight, natural and safe for children made of colorful laminate plywood, natural wood and local materials for learning activities. The desks should be in appropriate size and structure and easy to move. 2) The guidelines of area arrangement within the early childhood classroom supporting child-centered learning were that the center of classroom was separated by movable partitions to support the activities for Kindergarten 2 and 3. The partitions did not block the sound, but the vision for some activities. The area for both classrooms was organized in the same arrangement, the empty space at the center of the classroom as the area for free activity experiences or play corner activities. This was considered as the significant area to support child-centered learning.